SENI KARAWITAN YANG MANDIRI - Ening Sekarningsih (Paraguna, 2015)
Sundanese Karawitan is currently experiencing stagnation resulting from the foreign cultural influences thereby impacting the continuity of Karawitan itself.    Various attempts of preservation,    fostering, and development for Karawitan have continuously and sustainably been done by individuals, communities, and institutions for the sake of the continuity and eternity of the art.  One of Karawitan  arts  needs   to be preserved is Karawitan Mandiri that  comes from  people for  people"   such  as  the Gamelan   Ajeng/ Goong  Renteng,   Pantun   Beton   and  Tarawangsa.   Theexistence of such art is currently quite alarming so it is needed efforts to preserve to remain preferable and sought by various segments of society. It is required innovative and creative thinking by supporting artistsof Karawitan  Mandiri but is still grounded in the cultural roots of their regions.  Creativity and innovation performed on the folk arts are expected to lift up the art with local culture spirit into the art with national and even international spirit.   Ultimately the folk arts are able to become a local cultural asset and provide social welfare.